ENVIRONMENTAL IMPACTS (NEGATIVE AND POSITIVE) OF BREEDING IN COASTAL ENVIRONMENTS: EVALUATION FROM BIBLIOMETRIC ANALYSIS - de Oliveira Júnior, Marcos Antonio Cavalcante; Gomes, Érico Rodrigues [UNESP]; Rocha, Glairton Cardoso [UNESP] (Universidade Federal do Rio Grande do Norte - UFRN, 2021)
Shrimp farming has shown high growth in the last decades. In Brazil, most of the shrimp farming projects take place in coastal environments, specifically in mangrove areas. It aims to identify the main environmental impacts that shrimp farming has on coastal environments and thereby discuss mitigation measures. Bibliographic research was used, scientific productions published in national and international scientific journals between the years 2015 to 2019 and which developed studies on the environmental impacts of shrimp farming in coastal environments were verified. The Google Scholar database was used as keywords for the Portuguese terms “shrimp farming”, “environmental impact”, “degradation”. Initially, 504 academic productions. Twenty-one scientific articles were selected and published on the study proposal. The results indicate that the most frequent environmental impacts caused by the development of carciniculture are: deforestation and suppression of mangrove areas, contamination of water bodies, extinction of fishing species and other species of coastal fauna, intensification of the erosion process, among others. The main mitigating measures point to the implementation of environmental and business management and management strategies.
LOS IMPACTOS AMBIENTALES DE LA CARCINICULTURA EN AMBIENTES COSTEROS
IMPACTOS AMBIENTAIS (NEGATIVOS E POSITIVOS) DA CARCINICULTURA EM AMBIENTES COSTEIROS: AVALIAÇÃO A PARTIR DE ANÁLISE BIBLIOMÉTRICA
Keywords: Environmental Impacts; Mangroves; Shrimp farming